Modelling the spatial pattern of net primary productivity in Chinese forests - Jiang, Hong; Apps, Michael J; Zhang, Yanli; Peng, Changhui; Woodard, Paul M (Ecological Modelling, 1999)

Modelling the net primary productivity of temperate forest ecosystems in China with a GAP model - Jiang, Hong; Peng, Changhui; Apps, Michael J; Zhang, Yanli; Woodard, Paul M; Wang, Zhiming (Ecological Modelling, 1999)

Modelling the response of net primary productivity (NPP) of boreal forest ecosystems to changes in climate and fire disturbance regimes - Peng, Changhui; Apps, Michael J (Ecological Modelling, 1999)

Adapting a patch model to simulate the sensitivity of Central‐Canadian boreal ecosystems to climate variability - Price, D. T.; Halliwell, D. H.; Apps, M. J.; Peng, C. H. (Journal of Biogeography, 1999)
Summary Aim To investigate effects of within‐season and interannual climate variability on the behaviour of boreal forest ecosystems as simulated by the FORSKA2 patch model. Location Eleven climate station locations distributed along a transect across the boreal zone of central Canada. Methods FORSKA2′s water balance submodel was modified to enable it to behave more realistically under a varying climate. Long‐term actual monthly time‐series of temperature and precipitation data were detrended and used to drive the modified model. Long‐term monthly averages of the same detrended data were used to drive the unmodified model. Results Modifications created significant improvements when simulating species composition at sites in boreal Canada. Simulated forest biomass values were slightly higher than those obtained from the unmodified model using averaged climate records, but resembled the observed distribution of vegetation more closely. Main conclusions Modified FORSKA2 suggests that boreal forest composition and distribution may be more sensitive to changes in monthly rainfall data than to changes in temperature. Climate variability affects seasonal water balances and should be considered when using patch models to forecast vegetation dynamics during and following a period of climate transition. The modified model provided improved representation of the latitudinal trend in spatially averaged biomass density in this region.

Simulating effects of climate change on boreal ecosystem carbon pools in central Canada - Price, D. T.; Peng, C. H.; Apps, M. J.; Halliwell, D. H. (Journal of Biogeography, 1999)
Summary Aim Possible effects of current and future climates on boreal vegetation dynamics and carbon (C) cycling were investigated using the CENTURY 4.0 soil process model and a modified version of the FORSKA2 forest patch model. Location Eleven climate station locations distributed along a transect across the boreal zone of central Canada. Methods Both models were driven by detrended long‐term monthly climate data. Using a climate change signal derived from the GISS general circulation model (GCM) 2×CO 2 equilibrium climate scenario, the output from the two models was then used to compare simulated current and possible future total ecosystem C storage at the climate station locations. Results After allowing for their different underlying structures, comparison of output from both models showed good agreement with local field data under current climate conditions. CENTURY 4.0 was able to reproduce spatial variation in soil and litter C densities satisfactorily but tended to overestimate biomass productivity. FORSKA2 reproduced aboveground biomass productivity and spatially averaged biomass densities relatively well. Under the GISS 2×CO 2 scenario, both models generally predicted small increases in aboveground biomass C density for forest and tundra locations, but CENTURY 4.0 predicted greater decreases in soil and litter pools, for overall decreases in ecosystem C storage in the range 16–19%. Main conclusions With some caveats, results imply that effects of increased precipitation (as simulated by the GISS GCM) would more than compensate for any negative effects of increased temperature on forest growth. Increased temperature would also increase decomposition rates of soil and litter organic matter, however, for a net overall decrease in total ecosystem C storage.

Estimating changes in terrestrial vegetation and carbon storage - Peng, C.H; Guiot, J; Van Campo, E (Quaternary Science Reviews, 1998)

simulating carbon dynamics along the Boreal Forest Transect Case Study (BFTCS) in central Canada: 2. Sensitivity to climate change - Peng, Changhui; Apps, Michael J. (Global Biogeochemical Cycles, 1998)
The effects of climate change and doubling atmospheric CO 2 on carbon dynamics of the boreal forest in the area of the Boreal Forest Transect Case Study in central Canada were investigated using the process‐based plant‐soil model CENTURY 4.0. The results presented here suggest that (1) across the transect climate change would result in increased total carbon in vegetation biomass but decreased overall carbon in soil; (2) increased atmospheric CO 2 concentration under current climatic patterns would result in increased total carbon in vegetation and in soil organic matter; and (3) combined climate change and elevated CO 2 would increase both net primary productivity and decomposition rates relative to the current climate condition, but their combined action would be a reduction of soil carbon losses relative to those due to climate change alone. The interactive effects of climate change and elevated CO 2 , however, are not a simple additive combination of the individual responses. The responses to climate change and elevated CO 2 vary across the climate gradient from southern to northern sites on the transect. The present simulations indicate that the northern sites are more sensitive to climate change than the southern sites are, but these simulations do not consider likely changes in the disturbance regime or changes in forest species distribution.

Simulating carbon dynamics along the Boreal Forest Transect Case Study (BFTCS) in central Canada: 1. Model testing - Peng, Changhui; Apps, Michael J.; Price, David T.; Nalder, Ian A.; Halliwell, David H. (Global Biogeochemical Cycles, 1998)
CENTURY 4.0, a simulation model of carbon and nitrogen dynamics of terrestrial ecosystems based on the relationships between climate, soil texture, plant productivity, decomposition and human management, was tested against observed data along the boreal forest transect case study (BFTCS) in central Canada. The results show that the simulated average aboveground biomass and net N mineralization were consistent with observed data. The modeled estimates for soil carbon were consistent with those from regional‐scale empirical regression models. High correlation ( R 2 = 0.92) with data was obtained for the simulation of soil carbon dynamics of the boreal forest, but the model overestimated soil carbon (O–20 cm) by 2–8% for fine‐textured soil and underestimated soil carbon by 5–18% for sandy soil. The effects of climatic variation on temporal changes in biomass and soil carbon storage over the past century were found to be very different for southern and northern sites but relatively insensitive to site‐specific soil texture. The main discrepancies between observed data and CENTURY 4.0 results are associated with the effects of soil texture and an inadequate representation of fire disturbance on C dynamics of boreal forests. Further improvements, particularly in the representation of disturbance regimes and in the simulation of slow pool C dynamics, are suggested to enhance its predictive capability.

Contribution of China to the global carbon cycle since the last glacial maximum - Peng, Changhui; Apps, Michael J. (Tellus B: Chemical and Physical Meteorology, 1997)

Temporal and spatial variations of terrestrial biomes and carbon storage since 13 000 yr BP in Europe: Reconstruction from pollen data and statistical models - Peng, C. H.; Guiot, J.; Van Campo, E.; Cheddadi, R. (Water, Air, and Soil Pollution, 1995)

The Variation of Terrestrial Carbon Storage at 6000 yr BP in Europe: Reconstruction from Pollen Data Using Two Empirical Biosphere Models - Peng, C. H.; Guiot, J.; Van Campo, E.; Cheddadi, R. (Journal of Biogeography, 1995)

Reconstruction of past terrestrial carbon storage in the Northern Hemisphere from the Osnabrück Biosphere Model and palaeodata - Peng, Ch; Guiot, J; Van Campo, E (Climate Research, 1995)

The Vegetation Carbon Storage Variation in Europe Since 6000 BP: Reconstruction from Pollen - Peng, C. H.; Guiot, J.; Van Campo, E.; Cheddadi, R. (Journal of Biogeography, 1994)